2022
DOI: 10.1002/cbic.202200238
|View full text |Cite
|
Sign up to set email alerts
|

Tyramine Derivatives Catalyze the Aldol Dimerization of Butyraldehyde in the Presence of Escherichia coli

Abstract: Biogenic amine organocatalysts have transformed the field of synthetic organic chemistry. Yet despite their use in synthesis and to label biomolecules in vitro, amine organocatalysis in vivo has received comparatively little attention -despite the potential of such reactions to be interfaced with living cells and to modify cellular metabolites. Herein we report that biogenic amines derived from L-tyrosine catalyze the self-aldol condensation of butanal to 2-ethylhexenal -a key intermediate in the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…18,19 Building off of this work, we sought to expand upon the products accessible through the merger of biocatalysis and organocatalysis. Previous efforts to combine organocatalysis and biocatalysis include the synthesis of optically active diols, 20 aminolactones, 21 indole derivatives, 22 and aldol condensation products, 23 among others. 24 Toward our goal of synthesizing dinitroalkanes under mild conditions, we envisioned using an enzyme or whole-cell biocatalyst to produce an aldehyde from an alcohol substrate.…”
Section: Optimization Of Tandem Henry/michael Reactionmentioning
confidence: 99%
“…18,19 Building off of this work, we sought to expand upon the products accessible through the merger of biocatalysis and organocatalysis. Previous efforts to combine organocatalysis and biocatalysis include the synthesis of optically active diols, 20 aminolactones, 21 indole derivatives, 22 and aldol condensation products, 23 among others. 24 Toward our goal of synthesizing dinitroalkanes under mild conditions, we envisioned using an enzyme or whole-cell biocatalyst to produce an aldehyde from an alcohol substrate.…”
Section: Optimization Of Tandem Henry/michael Reactionmentioning
confidence: 99%
“…This is pertinent as synthetic biology approaches continue to produce compounds of industrial value, and because methods to diversify metabolites accessible via this approach are needed to replace petrochemical feedstocks [8–10] . To this end, we recently demonstrated the use of tyramine derivatives, and cellular amines from Corynebacterium glutamicum as biocompatible organocatalysts for the self‐aldol dimerisation of exogenous butyraldehyde in the presence of E. coli [11] . However, the use of biocompatible organocatalysis with engineered metabolic pathways in a living cell remains an outstanding challenge [9,12] .…”
Section: Figurementioning
confidence: 99%
“…To our knowledge, no enzyme is known to catalyse the α‐methylenation or α‐methylation of aldehydes in Nature, and 2‐MB/2‐MBA have never been accessed via microbial fermentation. Furthermore, we have recently reported that E. coli possesses a series of putative reductases in its genome with homology to ene‐reductases from Gluconobacter oxydans that can catalyze the reduction of α,ß‐unsaturated aldehydes, meaning 2‐MB could potentially be further processed to 2‐MBA via endogenous enzymes when generated in vivo (Table S15) [11] . In addition, we were inspired by recent seminal work by Goodwin et al.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations